2018
DOI: 10.1007/s11060-018-2868-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual changes in neurocognitive functioning and health-related quality of life in patients with brain oligometastases treated with stereotactic radiotherapy

Abstract: BackgroundRecently, it has been shown that at group level, patients with limited brain metastases treated with stereotactic radiotherapy (SRT) maintain their pre-treatment levels of neurocognitive functioning (NCF) and health-related quality of life (HRQoL). The aim of this study was to evaluate NCF and HRQoL changes over time at the individual patient level.MethodsNCF (seven domains assessed with a standardized test battery) and HRQoL (eight predetermined scales assessed with the EORTC QLQ-C30 and BN20 questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 41 publications
4
43
6
Order By: Relevance
“…The installation of a cranial imaging window was based on procedures described previously [39]. Mice (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) weeks old; n = 23) were anaesthetised using isoflurane and the head was stabilised in a stereotaxic frame (Kopf Instruments). Cerebral oedema was treated perioperatively with dexamethasone (2 μg/g body weight; intramuscular injection).…”
Section: Cranial Window Installation and Implantation Of Tumour Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The installation of a cranial imaging window was based on procedures described previously [39]. Mice (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) weeks old; n = 23) were anaesthetised using isoflurane and the head was stabilised in a stereotaxic frame (Kopf Instruments). Cerebral oedema was treated perioperatively with dexamethasone (2 μg/g body weight; intramuscular injection).…”
Section: Cranial Window Installation and Implantation Of Tumour Cellsmentioning
confidence: 99%
“…Treatment options are mainly limited to whole brain radiation, in some cases neurosurgery, and survival is poor [6,7]. Furthermore, patients with metastatic brain tumours present with neurological symptoms including cognitive impairment and epileptic seizures [8,9], and this can have a significant impact on quality of life. However, the pathophysiological mechanisms underlying the cause of neurocognitive impairment and tumour-associated epilepsy are poorly understood [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Baseline characteristics of patients with baseline HRQoL scores were not reported in two studies [39,40]. For two studies [33,36], a proportion of patients was also included in a subsequent study (respectively [32,37]). Sample sizes in the 9 selected studies ranged from 15 to 97 patients.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…In most studies, patients were female (range 43.2 to 67.3%), had primary lung cancer (range 37.3 to 100%), and had a median Karnofsky Performance Status (KPS) score of 80 (range < 70 to 100) ( Table 1). In four studies [34][35][36][37], patients with newly diagnosed BM were included; in four other studies [32,33,38,39], patients received prior BM treatment; and in one study [40], it was not reported if patients received prior BM treatment. Reasons for dropout were not reported in 6 studies [32,34,35,[38][39][40], and in two studies [36,37], reasons of dropout were reported, but without the numbers of patients (Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation